Analysis of nutrient deficiencies affecting in vitro growth and development of Eucalyptus dunnii Maiden - Oberschelp, Gustavo Pedro Javier; Gonçalves, Antônio Natal (2018)
Although basal medium optimization is a key factor in the success of tissue culture, its mineral composition is frequently disregarded when optimizing in vitro propagation protocols. A previous work on Eucalyptus dunnii micropropagation suggests that excessive callus formation and leaf chlorosis are related to specific nutritional conditions of the basal media. Recently, a novel basal medium based on the mineral nutrient analysis of E. dunnii young stump shoots was developed and successfully tested in plant regeneration and micropropagation of E. dunnii, avoiding all these issues. Considering this basal medium as an ideal growth condition, a mild deprivation of each macro and micronutrient and of the total organic fraction was imposed to E. dunnii in vitro cultures for 30 d. As a result, K, Mg, Mn, Cl, Zn, Mo, Ni or Co deprivation quantitatively affected growth and development of axillary shoots. Moreover, leaf chlorosis and the development of organogenic callus under Fe deficiency, and leaf drop along with shoot tip necrosis under N deficiency were observed. These symptoms suggest that nutrient content in E. dunnii tissues needs to be above 420.3 mg kg−1 for Fe and 27.7 g kg−1 for N to avoid the symptoms of leaf chlorosis and shoot tip necrosis. Additionally, the main role of Mn in quantitative responses and the antagonism between ions, especially for Mg/K and Mg/Zn, were denoted by the multivariate analysis. Overall, these results make a relevant contribution to the optimization of in vitro propagation of E. dunnii and other hard-to-propagate related species.